ZINC-BASED DENTAL CEMENTS: PROPERTIES, APPLICATIONS, AND ADVANCEMENTS - Alina Stefanache; Ionut Iulian Lungu; Radu Eduard Cernei; Oana Diana Popescu; Codrin Paul Fuioaga; Deleu Grigorii; Catalina Garbea; Smaranda Nazarie; Daniela Ivona Tomita; Cristian Mihalache; Oana Cucoveica; Calin Gabriela (Romanian Society of Oral Rehabilitation, 2023)
Aim of the study Zinc-based dental cements have played a significant role in restorative dentistry for several decades. These cements, including zinc phosphate, zinc oxide-eugenol (ZOE), and zinc polycarboxylate, offer unique properties and have been utilized in various clinical applications. Material and methods We performed an extensive exploration of pertinent scientific literature to gather information for the present review. Systematic searches were executed in electronic databases, such as PubMed, Google Scholar, and Web of Science, targeting articles released from April. The scope of the search focused on articles written exclusively in the English language. The search encompassed a comprehensive set of keywords and their various combinations, including "zinc-based dental cements," "properties," "applications," "advancements," "biocompatibility," "adhesion," "mechanical strength," "temporary restorations," "luting agents," "dental materials," and "clinical outcomes." Results zinc-based dental cements have demonstrated their significant potential as versatile materials in modern dentistry. Through a comprehensive exploration of their properties, applications, and advancements, it is evident that these cements offer a wide range of benefits for both practitioners and patients. Conclusions As research and development efforts persist, it is foreseeable that zinc-based dental cements will continue to evolve, further solidifying their role as integral components of successful dental treatments. With their ever-expanding applications and consistent improvements, these cements contribute significantly to the advancement of dental care, benefiting both practitioners and patients alike.